2014
DOI: 10.1007/s13139-013-0260-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in PET Image Interpretations Using Volumetric and Texture-based Quantification Methods in Nuclear Oncology

Abstract: Image quantification studies in positron emission tomography/computed tomography (PET/CT) are of immense importance in the diagnosis and follow-up of variety of cancers. In this review we have described the current image quantification methodologies employed in (18)F-fluorodeoxyglucose ((18)F-FDG) PET in major oncological conditions with particular emphasis on tumor heterogeneity studies. We have described various quantitative parameters being used in PET image analysis. The main contemporary methodology is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 125 publications
(165 reference statements)
0
58
1
2
Order By: Relevance
“…18 F-FDG PET data allow a quantitative evaluation of glucose metabolism of tumor. Although a lot of previous studies have reported the clinical usefulness using SUV max and volumetric parameters, these conventional parameter-based analyses have several limitations [4,5,[11][12][13]. These parameters are classified into histogram-based parameters, so they also have the short-comings of histogram analysis.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 F-FDG PET data allow a quantitative evaluation of glucose metabolism of tumor. Although a lot of previous studies have reported the clinical usefulness using SUV max and volumetric parameters, these conventional parameter-based analyses have several limitations [4,5,[11][12][13]. These parameters are classified into histogram-based parameters, so they also have the short-comings of histogram analysis.…”
Section: Patientsmentioning
confidence: 99%
“…Prior studies have shown the relationship between SUV max of 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) scan and histopathologic diagnosis [3]. Likewise, divergence of imaging analysis methods may lead to improved knowledge of tumor characterization [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several institutes have reported quantitative analysis studies, with a focus on radiomic features, for different imaging modalities such as computed tomography (CT),1, 2, 3 and magnetic resonance imaging (MRI) 4, 5, 6. The investigation of positron emission tomography (PET) radiomics was first reported in 2009 7, 8, 9. In recent years, fluorine‐18‐labeled fluoro‐2‐deoxy‐ d ‐glucose positron emission tomography–computed tomography, 18 F–FDG (PET/CT) has become a major functional imaging technique in oncology due to its ability to evaluate tumor stage and metabolic characteristics with high specificity and sensitivity 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…Thus, previous studies have investigated the associations between these mutations and SUV measures from PET images; however, there have been conflicting findings (18)(19)(20)(21)(22). These inconsistent reports may be due to the fact that simple SUV measures fail to capture the spatial relationships between image voxels, which may be more informative of the biology of these mutations and describe the degree of tumor heterogeneity (23,24). Highly heterogeneous tumors are often NOS 5 not otherwise specified.…”
mentioning
confidence: 99%